Testing nonlinearities with Finnish historical time series - Kari Takala; Matti Virén (Bank of Finland, 1993)
This paper contains a set of tests for nonlinearities in economic time series. The tests correspond both to standard diagnostic tests and some new developments in testing nonlinearities. The latter test procedures make use of models in chaos theory, so-called long memory models and some asymmetric adjustment models. Empirical tests are carried out with Finnish monthly data for ten macroeconomic time series covering the period 1920–1993. Test results support unambiguous the notion that there are nonlinearities in the data. Nonlinearities are detected not only in a univariate setting but also in some preliminary investigations dealing with a multivariate case. Certain differences seem to exist between nominal and real variables in nonlinear behaviour.
URN:NBN:fi:bof-201908131395
Keywords: 330